De Fabbroni a Chaptal: a fermentação do vinho entre o flogístico e a “nova química” - Pivetta, Marcos (2018)
The quest to improve the quality and increase the longevity of wines in France and in regions that are now part of Italy led some authors to write works on the production of this beverage between the second half of the 18th century and the beginning of the 19th. In this period, ordinary wines rarely lasted more than a year. Alcoholic fermentation is one of the aspects discussed with prominence in these books. In 1787 the Tuscan author Adamo Fabbroni (1748-1816) published in Florence Dell' arte di fare il vino, a book in which he formulates a theory on the fermentation of wine based on phlogistic ideas. In 1801, the French chemist Jean-Antoine Chaptal (1756-1832) published in Paris L 'art de faire le vin, a work dealing with winemaking from the perspective of the new chemistry of Antoine-Laurent Lavoisier (1743-1794). The objective of this thesis is to compare the visions of Fabbroni and Chaptal on wine fermentation and to show common points and divergences of these two authors about this chemical process at a time when the dominant ideas in this discipline made the transition from phlogistic conceptions to a "new chemistry "